Efektivitas terapi musik natural terhadap penurunan ansietas pasien penyakit jantung koroner yang menjalani angiografi koroner di RSPAD Gatot Soebroto - Suwito, Kafi Pangki; Jumaiyah, Wati; Natashia, Dhea (Poltekkes Kemenkes Aceh, 2025)
Background: Coronary artery disease (CAD) is one of the leading causes of cardiovascular morbidity and mortality worldwide, including in Indonesia. Coronary angiography as the gold standard for CAD diagnosis often triggers significant anxiety in patients, which may affect physiological stability and increase the risk of complications.Objective: This study aimed to evaluate the effectiveness of natural music therapy in reducing anxiety among CAD patients undergoing coronary angiography at RSPAD Gatot Soebroto.Methods: This quasi-experimental study employed a non-randomized control group pretest–posttest design. The study was conducted at RSPAD Gatot Soebroto, Jakarta, in 2024. A total of 30 patients were divided into intervention and control groups. The intervention group received 20 minutes of natural music therapy, while the control group did not receive any intervention. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI), and physiological parameters (blood pressure, heart rate, respiratory rate) were also assessed. Data were analyzed using paired t-test, Wilcoxon signed rank test, and Mann–Whitney U test with a significance level of α = 0,05.Results: The findings revealed a significant reduction in anxiety scores in the intervention group (mean difference = 24,13 ± 11,64; p = 0,000), whereas the control group showed no significant change (mean difference = 0,20 ± 3,19; p = 0.812). Between-group analysis demonstrated a statistically significant difference in anxiety reduction (p = 0,000). However, natural music therapy did not significantly influence physiological parameters.Conclusion: Natural music therapy was effective in reducing anxiety among CAD patients undergoing coronary angiography.